Adapting to the Era: Teaching Internet Language in Chinese Instruction in Kazakhstan Muhatai K. - Muhatai K.; Dossymbekova R.O. (Reviews of Modern Science, 2024)
In recent years, due to the increasingly close relationship between Kazakhstan and China, the cooperation between the two countries in politics, economy, culture, trade and other aspects has been expanding, and the frequent civil exchanges have enhanced influence of China in Kazakhstan, and the phenomenon of "Chinese learning fever" has also been reflected. In order to enable local Chinese learners to learn and master Chinese more smoothly, Chinese language teaching reform is imperative. With the rapid development of the Internet, network vocabulary has been greatly developed. The influence of online vocabulary has gradually penetrated into the daily life of the public from cyberspace. The era characteristics and social attributes of network vocabulary make it have a strong social expressiveness, and it should be valued by Chinese teaching circle. However, the current situation of teaching in Kazakhstan shows that the research and teaching of Internet vocabulary is not enough in the Chinese teaching circle. In the actual teaching application, Internet language is always facing the situation of being neglected. Based on this, this article hopes to attract the attention of Chinese teachers through the analysis of the necessity and function of Internet vocabulary in Chinese teaching, and provide some opinions and references for the research of online vocabulary and the development of Chinese teaching.